The Role of Community Policing Communication Programs in Strengthening Social Bonds in Kuwait - Yaqoub Yousef Alammar, خالد يعقوب (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
This study investigates the role of community policing programs in strengthening social cohesion within the State of Kuwait by assessing their impact across four principal domains: building trust between the police and the community, promoting cooperation, fostering national and social belonging, and facilitating the amicable resolution of conflicts. The research sample comprised 403 participants, including Kuwaiti citizens and residents, representing diverse age groups and educational backgrounds. Data were collected through a meticulously designed electronic questionnaire developed in accordance with relevant theoretical frameworks and prior studies. The findings revealed high mean scores across all examined domains, with “enhancing belonging” ranking first, followed by “building trust,” “promoting cooperation,” and “conflict resolution.,” respectively. The analysis further identified awareness programs, community meetings, and open channels of communication as the most influential components in reinforcing social cohesion. The results underscored the pivotal interactive role of community policing in engaging citizens in the maintenance of public security and in cultivating a collective sense of safety and belonging. The study concludes by recommending the expansion of public awareness programs, the training of police personnel in community-based mediation, and the incorporation of community policing principles into national educational curricula.